Characterization of multidrug resistance reversion in human colorectal adenocarcinoma cell lines - Lopes, João Eduardo Casalta (2010)
Introduction: Multidrug resistance (MDR) is a condition defined by the cross-resistance to several non-structurally related drugs, representing one of the major setbacks to the success of chemotherapy. One of the best studied MDR mechanisms is the overexpression of efflux pumps, such as P-glycoprotein (Pgp), multiple resistance-related protein 1 (MRP-1) and major vault protein (LRP). These proteins confer resistance to a large spectrum of similar substrates, despite their different extrusion mechanisms. Pharmacologic inhibition of MDR transporters is the major strategy to overcome this phenotype. Verapamil is an L-type calcium-channel blocker and a modulator for Pgp and MRP-1. L-buthionine-sulfoximine (BSO) is a γ-glutamylcysteine synthase inhibitor and can be used to functionally decrease MRP-1 activity. Aim: In this study we aim to compare transport kinetics for human colorectal adenocarcinoma cell lines, one sensitive and another resistant to chemotherapy, in the presence and absence of MDR reversers, using 99mTc-Sestamibi. Methods: MDR proteins expression was evaluated in sensitive (WiDr) and resistant (LS1034) human colorectal adenocarcinoma cell lines. Intracellular and plasma membrane Pgp and MRP1, and LRP expression was analyzed by flow-cytometry; Pgp expression was also analyzed by western blot. Cellular transport kinetics was analyzed in the presence and absence of MDR modulators, verapamil and BSO, using 99mTc-Sestamibi. Uptake and retention studies were performed using sensitive and resistant cells. MDR modulation was evaluated by performing retention studies in resistant cells after incubation with the referred drugs, for different time intervals (10 and 60 minutes) and concentrations (10, 25, 50 and 100 µM). Results: Pgp and MRP-1 expression was significantly higher (p<0.05) in resistant cells when comparing with the sensitive ones, although LRP was also expressed. Western blot studies confirmed flow-cytometry results. 99mTc-Sestamibi uptake and retention percentage were significantly higher (p<0.05) in the sensitive cell line, comparing with the resistant one for all time-points considered. In resistant cells incubated with MDR modulators there were no statistically significant differences (p>0.05) when considering the curves as a whole. However, for the first minutes after incubation with 99mTc-Sestamibi, there were differences among the MDR modulators used. Conclusions: In vitro kinetic studies using 99mTc-Sestamibi could be an indicator of MDR phenotype in colorectal adenocarcinoma cells. As the modulators used showed a reversion of the retention profile only for the first minutes, their administration should occur immediately before the administration of cytotoxic drugs.